Microbiota Revelations: First-time Prevotella spp. Identification in Iraq Pediatric Autism - Aladien Aurebi Muhawi / Yasin Yacoup Yousif. Al-Luaibi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2024)
Autism Spectrum Disorder (ASD) often co-occurs with gastrointestinal (GI) dysfunction, suggesting gut microbiota involvement. current study, the first in Iraq, investigated fecal microbiota in autistic children (n=18, aged 2-9 years) and neurotypical controls (n=27) in Basrah. Culture techniques detected facultative or aerobic bacteria, like E. coli, Enterococcus faecium, Lactococcus garvieae, Enterococcus faecalis ,Brevibacillus parabrevis, Lactobacillus salivarius, and Klebsiella pneumonia while Prevotella spp. in ASD were found to be lower by RT-qPCR. Which was statistical insignificance. These preliminary results point to possible changes in gut flora in Iraqi children diagnosed with ASD. Larger sample sizes and further study are required.